Disparities and barriers in the assessment of psychological distress, access to and use of psycho-oncological support in Europe: current perspectives - Coppini, Veronica; Ferraris, Giulia; Monzani, Dario; Grasso, Roberto; Pravettoni, Gabriella (Frontiers in Psychology, 2023)
The implementation of psycho-oncological support has shown important results in positively influencing treatment outcomes and quality of life in cancer patients and survivors. In the last few decades, the importance of mental health has been brought to attention to the general public and healthcare professionals on a national, institutional and organisational level. Official guidelines, policies, and training programs have been developed suggesting that psycho-oncological support should be considered as a non-negotiable requirement for quality cancer care in many hospitals and clinical centres across Europe. Health organisations, associations, institutions, and societies, such as the International Psycho-Oncology Society (IPOS) and the European Partnership for Action Against Cancer (EPAAC), are forming alliances, funding research projects and organising congresses in order to study, understand, and discuss the reasons for barriers and disparities in psycho-oncological support and, eventually, to overcome the existing cancer divide. Nevertheless, the World Health Organization's (WHO) estimations indicate that the cancer burden is still increasing, and relevant barriers and disparities in accessing psycho-oncological support continue to exist and influence the health conditions and quality of life of cancer patients and survivors. The present work will present the current disparities and barriers regarding assessment, access to and use of psycho-oncological support in the countries of the European Union, making suggestions for further research and possible solutions.